Flow Duration Curve for Downstream of Sungai Perak Using Minimum and Maximum Flow - Noh N.M.; Mohd Sidek L.; Razad A.Z.A.; Basri H.; Harun A.A.; Ismail M.A. (Springer, 2023)
The recent flood event that occurred in 2014 had caused disaster in Perak and Sungai Perak is the main river of Perak which is a major natural drainage system within the state. The aim of this paper is to determine the flow duration curve for downstream of Sungai Perak using minimum and maximum flow. The flow-duration curve describes the variability of the streamflow and is useful for determining dependable flow which information is required for planning of water resources and hydropower projects, designing a drainage system and flood control studies. In this study, the development of FDC is solely based on the available discharge data of the selected streamflow stations. The plot between percentage times of discharge against discharge was calculated using the probability equation to determine whether the percentage time of discharge is equal or exceeded. From the calculation, the results show that the significant differences in the discharge as the percentage of the time change. Two crucial stations were discussed which are Sungai Perak at Jambatan Iskandar station located at the main river and Sungai Pelus at Kampung Lintang station located at Sungai Perak main tributaries. The results shows that, half the time the flow in the river is at least 200m3/s, and 90% of the time not less than 100m3/s while the daily average flow at Kg Lintang was at least 20m3/s that is 50% of the time, and 10m3/s that is 90% of the time. It proves that the hydropower scheme gives a positive impact towards the downstream of the Chenderoh dam especially during the low flow where the flow is regulated by the discharge from the dam. 2020, Springer Nature Singapore Pte Ltd.